Non-enzymatic amperometric detection of phenol and catechol using nanoporous gold - Bui Thi Phuong Quynh; Byun, Ji Young; Kim, Sang Hoon (ELSEVIER SCIENCE SA, 2015)
Nanoporous gold (NPG) thin films were found to be capable of directly and reliably sensing phenol and catechol using amperometric technique at neutral conditions without enzyme. The sensing of phenol and catechol was conducted on NPG based on their different electro-oxidation potentials. The NPG thin films exhibited not only good sensitivities but also large linear detection ranges in comparison with the current state of the art enzyme-based electrodes. They also had a good resistance against surface fouling, enabling detection at neutral conditions. A good selectivity over various organic and inorganic interfering agents was also recorded. In particular, although NPG appeared to be a good sensor for both phenol and catechol, it was found that the NPG was able to selectively determine catechol in the presence of phenol at an appropriate applied voltage. The achieved results offer potentially promising and simple non-enzymatic amperometric detection of phenolic compounds in industrial and environmental analyses using NPG thin film based electrodes. (C) 2015 Elsevier B.V. All rights reserved.
Keywords: PLATINUM THIN-FILMS; ELECTROCHEMICAL DETECTION; OXIDATION; SENSOR; HYDROQUINONE; ELECTRODES; BIOSENSOR